Preparation method of carbide-reinforced CoCrFeNi high-entropy alloy

By adding TiC to CoCrFeNi high-entropy alloy and using high-temperature smelting, rolling and annealing treatment methods, a carbide-enhanced high-entropy alloy with excellent strength was prepared, which solved the problem of low alloy strength and achieved significant strength and toughness improvement.

CN119710424APending Publication Date: 2025-03-28WUHAN UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411914701.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

CoCrFeNi high-entropy alloys have low strength, and the prior art improves strength by alloying or adding carbide phases, but the plasticity is reduced and the strength is limited.

Method used

By adding hard TiC, high-entropy alloys composed of alloy matrix phase and multiphase multi-scale carbides are prepared by high-temperature smelting, rolling and annealing treatment, and the microstructure of the alloy is regulated to improve strength and toughness.

Benefits of technology

The comprehensive room temperature toughness and toughness of the alloy have been significantly improved, with a yield strength of 0.68~1.4GPa, an ultimate tensile strength of 0.85~1.5GPa, and an elongation of 1~22%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710424A_ABST
    Figure CN119710424A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a carbide-reinforced CoCrFeNi high-entropy alloy, and belongs to the technical field of metal materials and machining.Hard TiC is added, and the high-entropy alloy composed of an alloy matrix phase and multi-phase multi-scale carbides is prepared through high-temperature smelting, rolling and annealing treatment. A matrix phase is dynamically recrystallized through rolling and annealing treatment, a fine and dispersed carbide particle phase is separated out, the obdurability comprehensive performance of the alloy is improved under the action of fine grain strengthening and second phase strengthening of carbide, and the carbide-reinforced CoCrFeNi high-entropy alloy with excellent obdurability is prepared and is expected to be applied to aerospace structural parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a waste gas carbide reinforced CoCrFeNi high entropy alloy, belonging to the technical field of metal materials and processing. Background Art

[0002] Entropy alloys are composed of multiple principal elements, have high mixing entropy and lattice distortion, and exhibit a series of excellent properties, such as excellent wear and corrosion resistance, high temperature stability, electrical and thermal conductivity, etc. These superior properties make high entropy alloys have broad industrial application prospects. CoCrFeNi high entropy alloy is one of the earliest and most studied alloys. It has a single-phase structure of face-centered cubic structure (FCC). Its excellent room temperature plasticity and slightly higher strength than traditional alloys have attracted great interest from scientific researchers at home and abroad. However, with the in-depth development of research and the increasing demand for material performance in the manufacturing industry, the problem of low strength of CoCrFeNi high entropy alloy has become increasingly prominent.

[0003] In order to strengthen CoCrFeNi high entropy alloy, alloying, heat treatment, mechanical hot deformation and other methods are usually used. By alloying to form solid solution elements or a second phase, the strength of the alloy is improved under the action of solid solution strengthening or second phase strengthening. He et al. prepared CoCrFeNiNbx eutectic high entropy alloy by adding Nb element smelting. It is a two-phase eutectic structure of FCC matrix and lamellar Laves phase, which has higher casting performance and strength performance than CoCrFeNi alloy; however, due to the formation of Laves brittle phase, the plasticity of the eutectic alloy is reduced by about 40% (He JY, Liu WH, Wang H., et al. Effects of Nb additions on the microstructure and mechanical property of CoCrFeNi high-entropy alloys. Intermetallics, 2015, 60: 1-8). High-hardness carbide phase is also often introduced as a second phase to improve the mechanical properties of high-entropy alloys. For example, Huang et al. added 10 vol.% TiC to CoCr3Fe5Ni alloy, and the yield strength of the alloy obtained by smelting increased by 30%, and the tensile strength increased by 23%, which were 401 MPa and 795 MPa, respectively, and the elongation was reduced to 17% (Huang S., Zhang J., Wu H., et al. Boosted mechanical properties of CoCr3Fe5Ni high entropy alloy via in-situ TiC particles. Journal of Alloys and Compounds, 2023, 968: 172051). Adding 5 vol% TiC to CoCrFeNi alloy increases the yield strength of CoCrFeNiTiC alloy to 550 MPa, and reduces the elongation to 16% (Zhang J., Jia T., Qiu H., et al. Effect of cooling rateupon the microstructure and mechanical properties of in-situ TiC reinforcedhigh entropy alloy CoCrFeNi. Journal of Materials Science&Technology, 2020, 42: 122-129).In summary, the strength of the alloy can be improved by introducing the second phase through alloying method or directly adding carbides, but the plasticity of the alloy is reduced and the strength improvement is limited. The yield strength of TiC / CoCr3Fe5Ni and TiC / CoCrFeNi alloys are only about 400MPa and 550MPa.

[0004] The dual-phase high entropy alloy is processed by rolling and annealing to improve the strength of the alloy while maintaining good plasticity. 0.45 The CoCrFeNi dual-phase high entropy alloy was cold rolled 70% and annealed. After annealing, the matrix phase was dynamically recrystallized, and fine particles were precipitated in the alloy. Under the effect of fine grain strengthening and precipitation strengthening, the yield strength of the alloy increased from 209MPa in the cast state to 727MPa, and the elongation was 22% (Hou J., Wang Z., Shi X., et al. Strengthening of an Al 0.45 CoCrFeNi high-entropy alloy via in situfabricated duplex-structured composites.Journal of Materials Science,2020,55:7894-7909). The rolling and annealing treatment of this dual-phase high-entropy alloy provides theoretical guidance for improving the strength of CoCrFeNi high-entropy alloy. Summary of the invention

[0005] In view of the problem of low strength of CoCrFeNi high entropy alloy, the present invention proposes to add hard TiC, and obtain a high entropy alloy composed of an alloy matrix phase and multi-phase multi-scale carbides through high-temperature smelting, rolling and annealing. The matrix phase undergoes dynamic recrystallization through rolling and annealing, and a fine and dispersed carbide particle phase is precipitated. Under the effect of fine grain strengthening and second phase strengthening of carbides, the comprehensive strength and toughness of the alloy is improved, and a carbide-reinforced CoCrFeNi high entropy alloy with excellent strength and toughness is obtained.

[0006] In order to solve the above technical problems, the present invention provides a carbide-reinforced CoCrFeNi high entropy alloy, wherein the alloy consists of a high entropy alloy phase with a face-centered cubic structure and a carbide phase; the high entropy alloy phase is an FCC solid solution composed of Co, Cr, Fe, Ni and Ti elements; the carbide phase is (Cr, Co, Fe, Ni, Ti) 23 A mixture of C6 solid solution and (Ti,Cr,Co,Fe,Ni)C solid solution, (Cr,Co,Fe,Ni,Ti) 23The atomic ratio of Cr, Co, Fe, Ni, Ti and C in C6 solid solution is (50-53): (9-10): (8-10): (5-8): (1-2): (21-23); the atomic ratio of Ti, Co, Fe, Ni, Cr and C in (Ti, Cr, Co, Fe, Ni)C solid solution is (20-22): (8-10): (8-10): (7-9): (8-10): (43-45).

[0007] As an improvement of the above technical solution, the microstructure of the high entropy alloy consists of a dendritic high entropy alloy phase, micron-sized carbide particles between dendrites, and micro-nano carbide particles precipitated by annealing, and the phase interfaces are well bonded.

[0008] A method for preparing any of the above-mentioned carbide-reinforced CoCrFeNi high-entropy alloys comprises the following steps: weighing Co metal powder, Cr metal powder, Fe metal powder, Ni metal powder and TiC powder according to the atomic ratio of (0.95-1.05):(0.95-1.05):(0.95-1.05):(0.1-0.3), mixing them evenly and then smelting them at high temperature to obtain a cast alloy; rolling the cast alloy for multiple passes at room temperature, with the total rolling amount not less than 50%; annealing the rolled alloy to obtain a carbide-reinforced CoCrFeNi high-entropy alloy.

[0009] As a preferred embodiment of the above technical solution, the method for preparing the carbide-reinforced CoCrFeNi high-entropy alloy provided by the present invention further includes some or all of the following technical features:

[0010] As an improvement of the above technical solution, the purity of the Co metal powder, Cr metal powder, Fe metal powder, Ni metal powder and TiC powder raw materials is greater than 99.9%, the particle size range of the powder is 0.05-200μm, and the powder raw materials are mixed evenly.

[0011] As an improvement of the above technical solution, the high temperature smelting method is any one of arc melting or vacuum induction melting, and the melting temperature is 1500°C≤2500°C.

[0012] As an improvement of the above technical solution, in the multi-pass rolling process, the rolling reduction of each pass is 5-10%, and the total rolling amount is not less than 50%. The multi-pass rolling process can be multi-pass cold rolling, multi-pass hot rolling or a mixed operation of cold rolling and hot rolling.

[0013] As an improvement of the above technical solution, the annealing treatment is carried out in a vacuum atmosphere or an argon atmosphere, the annealing temperature is 600-900° C., the insulation time is 0.5-2 hours, and the cooling method is water cooling.

[0014] The properties of the carbide-reinforced CoCrFeNi high-entropy alloy as described above are excellent in terms of comprehensive strength and toughness at room temperature, with a yield strength of 0.68 to 1.4 GPa, an ultimate tensile strength of 0.85 to 1.5 GPa, and an elongation of 1 to 22%.

[0015] Taking into account the strengthening effect of carbides and the advantages of rolling and annealing technology, the present invention designs and prepares a new type of carbide reinforced CoCrFeNi high entropy alloy, adopts high-temperature smelting, rolling and annealing methods to control the microstructure of the alloy, and obtains a high-entropy alloy material with excellent toughness, which is expected to be used in aerospace structural parts.

[0016] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0017] 1. The present invention uses powder raw materials to prepare carbide-reinforced CoCrFeNi high-entropy alloys through high-temperature smelting technology. The powders are evenly mixed, the reaction is sufficient during the smelting process, the smelting efficiency is effectively improved, and the microstructure of the alloy is more uniform than when the bulk raw materials are smelted. At the same time, the smelting temperature is reasonably controlled between the melting point and boiling point of the pure metal to avoid the loss of metal raw materials and improve the accuracy of the composition.

[0018] 2. The present invention adopts rolling and annealing methods to control the microstructure of the cast alloy and improve the strength and toughness of the alloy. The alloy is plastically deformed by rolling, and the dislocation density is greatly increased, resulting in a work hardening effect and improving the strength; the internal dislocations of the alloy are reorganized or eliminated by annealing to restore the toughness of the material. When annealing at a certain temperature, the alloy phase undergoes partial recovery and recrystallization, part of the grains form fine recrystallized grains, and part of the grains retain high-density dislocations, which jointly improve the strength and toughness of the alloy under the effects of dislocation strengthening and grain refinement. At the same time, during the annealing process, fine and dispersed second-phase carbide particles are precipitated from the supersaturated alloy phase, further improving the strength of the alloy under the effect of dispersion strengthening.

[0019] 3. The present invention prepares a new type of carbide-reinforced CoCrFeNi high entropy alloy system, which is composed of a highly plastic alloy phase, micron-sized carbide particles and micro-nano carbide particles precipitated by annealing, with uniform organizational structure and stable mechanical properties. The alloy has excellent room temperature strength and toughness comprehensive properties, with a yield strength of 0.68-1.4GPa, an ultimate tensile strength of 0.85-1.5GPa, and an elongation of 1-22%.

[0020] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the following is a detailed description in combination with the preferred embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings of the embodiment are briefly introduced below.

[0022] Figure 1 Schematic diagram of rolling and heat treatment of the carbide-reinforced CoCrFeNi high entropy alloy of the present invention;

[0023] Figure 2 This is the XRD spectrum of the carbide-reinforced CoCrFeNi high-entropy alloy prepared in Example 1 of the present invention:

[0024] Figure 3 (a) is a microstructure diagram of the carbide-reinforced CoCrFeNi high entropy alloy prepared in Example 1 of the present invention:

[0025] Figure 3 (b) is a microstructure diagram of the carbide-reinforced CoCrFeNi high entropy alloy prepared in Example 2 of the present invention:

[0026] Figure 3 (c) is a microstructure diagram of the carbide-reinforced CoCrFeNi high entropy alloy prepared in Example 3 of the present invention:

[0027] Figure 3 (d) is a microstructure diagram of the carbide-reinforced CoCrFeNi high entropy alloy prepared in Example 4 of the present invention;

[0028] Figure 4 It is a tensile stress-strain curve diagram of the carbide-reinforced CoCrFeNi high entropy alloy of the present invention. DETAILED DESCRIPTION

[0029] The specific implementation modes of the present invention are described in detail below, which is a part of this specification. The principles of the present invention are explained through examples. Other aspects, features and advantages of the present invention will become clear through the detailed description.

[0030] The present invention adds hard TiC to the CoCrFeNi high entropy alloy, and obtains a high entropy alloy composed of an alloy matrix phase and carbides by high-temperature smelting; further, the matrix phase is dynamically recrystallized by rolling and annealing, and a fine and dispersed carbide particle phase is precipitated; through fine grain strengthening and the second phase strengthening effect of two carbides, the comprehensive strength and toughness properties of the alloy are improved, and a carbide-reinforced CoCrFeNi high entropy alloy with excellent room temperature strength and toughness is obtained. The specific embodiments of the present invention are described in detail below, which is a part of this specification, and the principles of the present invention are explained by examples. Other aspects, features and advantages of the present invention will become clear through this detailed description.

[0031] Embodiment 1:

[0032] Preparation of CoCrFeNi(TiC) 0.1 High entropy alloy. The specific steps are as follows:

[0033] (1) High temperature smelting: 200 g of pure metal powders of Co, Cr, Fe, Ni and TiC with a purity of 99.9% were weighed according to the molar ratio of Co / Cr / Fe / Ni / TiC of 0.95:1.05:1:1:0.1. The particle size of each pure metal powder was 5 μm, and the particle size of TiC powder was 200 μm. The powder raw materials were manually mixed for 20 minutes to obtain a mixed powder. Then, the mixed powder was pressed into a block and smelted at 1500°C in a vacuum induction melting furnace to obtain a cast alloy.

[0034] (2) Room temperature cold rolling: The as-cast alloy sample obtained in step 1 was cold rolled at room temperature, with each rolling reduction being 10% and the total rolling reduction being 75%.

[0035] (3) Annealing treatment: The cold-rolled alloy sample was placed in a tube furnace and annealed at 800°C for 2 h in an argon atmosphere, and then taken out and quenched in water to room temperature to obtain CoCrFeNi(TiC) 0.1 High entropy alloy.

[0036] Figure 2 Curve (a) is the CoCrFeNi(TiC) prepared in Example 1 0.1 XRD pattern of high entropy alloy, mainly FCC high entropy alloy phase and (Ti,Cr,Co,Fe,Ni)C carbide phase. (Cr,Co,Fe,Ni,Ti) 23 The content of C6 carbide phase is low and is not shown in the XRD pattern. 0.1 The high entropy alloy is composed of FCC high entropy alloy phase, micron-sized (Ti, Cr, Co, Fe, Ni) C and (Cr, Co, Fe, Ni, Ti) 23 C6 carbide particles and annealed micro-nano (Cr, Co, Fe, Ni, Ti) 23 C6 carbide particle composition (such as Figure 3 (a)); the alloy has a yield strength of 0.68 GPa, an ultimate tensile strength of 0.85 GPa, and an elongation of 22% ( Figure 4 (Curve a) is the CoCrFeNi(TiC) prepared in Example 1 0.1 Stress-strain curve of high entropy alloy).

[0037] Embodiment 2:

[0038] Preparation of CoCrFeNi(TiC) 0.2High entropy alloy. The specific steps are as follows:

[0039] (1) High temperature smelting: 200 g of pure metal powders of Co, Cr, Fe, Ni and TiC with a purity of 99.9% were weighed according to the molar ratio of Co / Cr / Fe / Ni / TiC of 1.05:0.95:0.95:1.05:0.2. The particle size of each pure metal powder was 44 μm, and the particle size of TiC powder was 10 μm. The powder raw materials were manually mixed for 15 minutes to obtain a mixed powder. Then, the mixed powder was pressed into a block and smelted in an arc melting furnace at 2200°C to obtain a cast alloy.

[0040] (2) Two-step rolling: The as-cast alloy sample obtained in step 1 was rolled at 1150°C, with a rolling reduction of 6% per pass and a hot rolling reduction of 40%. It was then kept at 900°C for 1 hour and cold rolled at room temperature, with a rolling reduction of 10% per pass and a cold rolling reduction of 60%.

[0041] (3) Annealing: The rolled alloy sample was placed in a tube furnace and annealed at 600°C for 1 h in an argon atmosphere. Afterwards, the sample was taken out and quenched in water to room temperature to obtain CoCrFeNi(TiC) 0.2 High entropy alloy.

[0042] Figure 2 Curve (b) is the CoCrFeNi(TiC) prepared in Example 2 0.2 XRD pattern of high entropy alloy, mainly FCC high entropy alloy phase and (Ti,Cr,Co,Fe,Ni)C carbide phase. (Cr,Co,Fe,Ni,Ti) 23 The content of C6 carbide phase is low and is not shown in the XRD pattern. 0.2 The high entropy alloy is composed of FCC high entropy alloy phase, micron-sized (Ti, Cr, Co, Fe, Ni) C carbides, and annealed (Ti, Cr, Co, Fe, Ni) C and (Cr, Co, Fe, Ni, Ti) 23 C6 carbide particle composition (such as Figure 3 (b)); the alloy has high strength, yield strength of 1.4GPa, ultimate tensile strength of 1.5GPa, plastic strain of 1% ( Figure 4 (Curve b) is the CoCrFeNi(TiC) prepared in Example 2 0.2 Stress-strain curve of high entropy alloy).

[0043] Embodiment 3:

[0044] Preparation of CoCrFeNi(TiC) 0.2 High entropy alloy. The specific steps are as follows:

[0045] (1) High temperature smelting: 200 g of pure metal powders of Co, Cr, Fe, Ni and TiC with a purity of 99.9% were weighed according to the molar ratio of Co / Cr / Fe / Ni / TiC of 1:1:1.05:0.95:0.2. The particle size of each pure metal powder was 44 μm, and the particle size of TiC powder was 5 μm. The powder raw materials were manually mixed for 10 minutes to obtain a mixed powder. Then, the mixed powder was pressed into a block and smelted in an arc melting furnace at 2000°C to obtain a cast alloy.

[0046] (2) Room temperature cold rolling: The cast alloy sample obtained in step 1 is rolled at room temperature, with each rolling reduction being 10% and the total rolling reduction being 50%.

[0047] (3) Annealing: The rolled alloy sample was placed in a tube furnace and annealed at 900°C for 1 h in an argon atmosphere. Afterwards, the sample was taken out and quenched in water to room temperature to obtain CoCrFeNi(TiC) 0.2 High entropy alloy.

[0048] Figure 2 Curve (c) is the CoCrFeNi(TiC) prepared in Example 3 0.2 XRD pattern of high entropy alloy, mainly FCC high entropy alloy phase and (Ti,Cr,Co,Fe,Ni)C carbide phase. (Cr,Co,Fe,Ni,Ti) 23 The content of C6 carbide phase is low and is not shown in the XRD pattern. 0.2 The high entropy alloy is composed of FCC high entropy alloy phase, micron-sized (Ti, Cr, Co, Fe, Ni) C and (Cr, Co, Fe, Ni, Ti) 23 C6 carbide, and annealed micro-nano (Cr, Co, Fe, Ni, Ti) 23 C6 carbide particle composition (such as Figure 3 (c)); the yield strength of the alloy is 0.75GPa, and the plastic strain is 13% ( Figure 4 (Curve c) is the CoCrFeNi(TiC) prepared in Example 3 0.2 Stress-strain curve of high entropy alloy).

[0049] Embodiment 4:

[0050] Preparation of CoCrFeNi(TiC) 0.3 High entropy alloy. The specific steps are as follows:

[0051] (1) High temperature smelting: 200 g of pure metal powders of Co, Cr, Fe, Ni and TiC with a purity of 99.95% were weighed according to the molar ratio of Co / Cr / Fe / Ni / TiC of 1:1.05:1:0.95:0.3, the particle size of Fe was 0.05 μm, the particle size of other pure metal powders was 20 μm, and the particle size of TiC powder was 44 μm; the powder raw materials were manually mixed for 10 minutes to obtain a mixed powder. Then, the mixed powder was pressed into a block and smelted in an arc melting furnace at 2500°C to obtain a cast alloy.

[0052] (2) High temperature hot rolling: The as-cast alloy sample obtained in step 1 was hot rolled at 1150° C., with a rolling reduction of 5% per pass and a total rolling reduction of 50%.

[0053] (3) Annealing: The rolled alloy sample was placed in a tube furnace and annealed at 700°C for 0.5 h in a vacuum atmosphere, and then taken out and quenched in water to room temperature to obtain CoCrFeNi(TiC) 0.3 High entropy alloy.

[0054] Figure 2 Curve (d) is the CoCrFeNi(TiC) prepared in Example 4 0.3 XRD pattern of high entropy alloy, mainly FCC high entropy alloy phase and (Ti,Cr,Co,Fe,Ni)C carbide phase. (Cr,Co,Fe,Ni,Ti) 23 The content of C6 carbide phase is low and is not shown in the XRD pattern. 0.3 The high entropy alloy is composed of FCC high entropy alloy phase, micron-sized (Ti, Cr, Co, Fe, Ni) C and (Cr, Co, Fe, Ni, Ti) 23 C6 carbide, and annealed (Ti,Cr,Co,Fe,Ni)C and (Cr,Co,Fe,Ni,Ti) 23 C6 carbide particle composition (such as Figure 3 (d)); the yield strength of the alloy is 0.70GPa and the elongation is 11% ( Figure 4 (Curve d) is the CoCrFeNi(TiC) prepared in Example 3 0.3 Stress-strain curve of high entropy alloy).

[0055] The above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and changes can be made without departing from the principle of the present invention, and these improvements and changes are also regarded as the protection scope of the present invention.

Claims

1. A carbide-reinforced CoCrFeNi high-entropy alloy, characterized in that: The carbide-reinforced CoCrFeNi high-entropy alloy consists of a high-entropy alloy phase with a face-centered cubic structure and a carbide phase; the high-entropy alloy phase is an FCC solid solution composed of Co, Cr, Fe, Ni and Ti elements.

2. The carbide-reinforced CoCrFeNi high entropy alloy according to claim 1, characterized in that: The carbide phase is (Cr, Co, Fe, Ni, Ti) 23 A mixture of C6 solid solution and (Ti,Cr,Co,Fe,Ni)C solid solution, wherein (Cr,Co,Fe,Ni,Ti) 23 The atomic ratio of Cr, Co, Fe, Ni, Ti and C in C6 solid solution is (50-53): (9-10): (8-10): (5-8): (1-2): (21-23); the atomic ratio of Ti, Co, Fe, Ni, Cr and C in (Ti, Cr, Co, Fe, Ni)C solid solution is (20-22): (8-10): (8-10): (7-9): (8-10): (43-45).

3. The carbide-reinforced CoCrFeNi high entropy alloy according to claim 1, characterized in that: The microstructure of the high entropy alloy consists of a dendrite-shaped high entropy alloy phase, micron-sized carbide particles between dendrites, and micro-nano carbide particles precipitated by annealing, and the phase interface is well bonded.

4. A method for preparing a carbide-reinforced CoCrFeNi high entropy alloy, characterized in that: The following steps are included: Co metal powder, Cr metal powder, Fe metal powder, Ni metal powder and TiC powder are uniformly mixed and then smelted at high temperature to obtain a cast alloy; the cast alloy is rolled for multiple passes at room temperature, and the total rolling amount is not less than 50%; the rolled alloy is annealed to obtain a carbide-reinforced CoCrFeNi high entropy alloy.

5. The method for preparing the carbide-reinforced CoCrFeNi high entropy alloy according to claim 1, characterized in that: The atomic ratio of the Co metal powder, Cr metal powder, Fe metal powder, Ni metal powder and TiC powder is (0.95-1.05):(0.95-1.05):(0.95-1.05):(0.95-1.05):(0.1-0.3).

6. The method for preparing the carbide-reinforced CoCrFeNi high entropy alloy according to claim 1, characterized in that: The raw material purity of the Co metal powder, Cr metal powder, Fe metal powder, Ni metal powder and TiC powder is greater than 99.9%, and the particle size range of the powder is 0.05-200 μm.

7. The method for preparing the carbide-reinforced CoCrFeNi high entropy alloy according to claim 1, characterized in that: The high temperature melting method is any one of arc melting or vacuum induction melting, and the melting temperature is 1500°C≤2500°C.

8. The method for preparing the carbide-reinforced CoCrFeNi high entropy alloy according to claim 1, characterized in that: In the multi-pass rolling process, the rolling reduction in each pass is 5-10%, and the total rolling reduction is not less than 50%; the multi-pass rolling process can be multi-pass cold rolling, multi-pass hot rolling or a mixed operation of cold rolling and hot rolling.

9. The method for preparing the carbide-reinforced CoCrFeNi high entropy alloy according to claim 1, characterized in that: The annealing treatment is carried out in a vacuum atmosphere or an argon atmosphere, the annealing temperature is 600-900° C., the holding time is 0.5-2 hours, and the cooling method is water cooling.

10. The carbide-reinforced CoCrFeNi high entropy alloy according to any one of claims 1 to 9, characterized in that: The carbide reinforced CoCrFeNi high entropy alloy has a yield strength of 0.68 to 1.4 GPa, an ultimate tensile strength of 0.85 to 1.5 GPa, and an elongation of 1 to 22%.

Citation Information

Patent Citations

  • Preparation method for high-entropy alloy composite material with externally-added nanometer ceramic phase reinforced and toughened

    CN105648297A

  • Preparation method of metastable state high-entropy alloy with high-strength and high-plasticity heterogeneous grain structure

    CN115976349A

  • Durable high-entropy alloy punch and preparation method thereof

    CN117965992A

  • Low-cost high-performance FeMnCrNi-based high-entropy alloy as well as preparation method and application thereof

    CN118186272A

  • Multi-scale heterogeneous ceramic phase reinforced high-entropy alloy and preparation method thereof

    CN118703857A